Snakes and Stairs Game Design using Automata Theory - Raj, N; Dubey, R (International Journal of Computer Sciences and Engineering, 2025)
Game design using automata tools and game theory analysis has been works from decades but there are a very few works on dynamic input or dynamic state generation. This paper summarizes game design of a traditional Snake and Ladder board game in a modernized way using the study of automata theory and game theory too, for both android and computer platforms with generation of random inputs which are also explained using flowcharts, DFSA and NDFSA.